Evaluation of the Monocyte Chemoattractant Protein-1 Gene (rs1024611) Polymorphism in Burn Wound Patients - Hasan Fadhil Kudhair; Abeer Thaher Naji Al-Hasnawi; Ali Jalil Ali Alyassery (Biomedical and Biotechnology Research Journal, 2024)
Background: Burns are described as heat- or acute trauma-induced skin injuries or other body tissue. One cytokine that promotes inflammation is monocyte chemoattractant protein-1 (MCP-1), which is essential to the inflammatory process. This study aimed to investigate the relationship between the genetic variation of MCP-1-2518A/G and the severity of bacterial infection in burn wounds. Methods: A case–control study included 35 burn wound patients and 35 healthy people as a control group. Whole blood was used for DNA extraction. DNA extraction was used to detect the MCP1 gene (rs1024611) polymorphism using conventional polymerase chain reaction. Results: Regarding the genotypes of the MCP1 gene (rs1024611) polymorphism, there were statistical differences (P = 0.008) between the groups under study. In patients, compared to controls, the AA genotype was higher, whereas it was discovered that controls had a higher frequency of the AG and GG genotypes than did patients. In addition, patients’ “A” allele levels were higher than those of controls. On the contrary, the patients’ “G” allele was lower than that of the control group, with a significant difference (P = 0.001). Conclusion: The result of this study has shown that in patients, the AA genotype was higher than in controls. Therefore, the MCP1 gene (rs1024611) polymorphism may have a protective role in burn wound bacterial infection.